Pengaruh Reputasi KAP, Opini Audit, Profitabilitas, dan Kompleksitas Operasi Perusahaan Terhadap Audit Delay (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2015-2017) - Sari, Ni Komang Mita Abdina; Sujana, Edy (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
The purpose of this study was to empirically prove the impact of KAP reputation, audit opinion, profitability, and complexity of company operations toward audit delay. This study was a quantitative study using secondary data obtained from the company's annual report. The population of this study were all mining sector companies listed on the Indonesia Stock Exchange during the 2015-2017 period. The sampling technique in this study was purposive sampling. The samples that qualified the purposive sampling criteria in this study were 17 companies. The data analysis technique used was multiple linear regression analysis using SPSS software version 24. The results showed that (1) KAP reputation had an effect toward audit delay, (2) audit opinion had an effect toward audit delay, (3) profitability had an effect toward audit delay, and (4) complexity of company operations had an effect toward audit delay.